Makna Simbolik Appassili Tujuh Bulanan di Pasuleang II Kabupaten Takalar - Nurfadilah Nurfadilah; Hajrah Hajrah; Andi Fatimah Yunus (Indonesian Journal of Pedagogical and Social Sciences, 2022)
Abstract. The purpose of this study is to describe the meaning of icons, indices and symbols contained in the process of implementing the seven-monthly appassili in Pasuleang II Takalar Regency seen from Charles Sanders Peirce's semiotic theory. This type of research is qualitative research. The data in this study is a form of interpretation related to the meaning contained in the symbols used in the seven monthly appassili in Pasuleang II Takalar District. Sources of data in this study using data sources or informants who act as information centers. The methods used in collecting this research data are observation, interviews and documentation. The results of this study are as follows. The meaning of icons contained in the seven-monthly appassili procession are: (1) buras (burasak), (2) white and black glutinous rice / songkolok (songkolok kebok na lekleng), (3) native chicken (jangang kampong), (4) betel leaf (lekok). The meaning of the index contained in the seven-monthly appassili procession lies in the procession of the tradition, namely: (1) paddupang, (2) bathing, (3) wearing clean clothes, (4) reading appassili intentions and prayers of kindness, (5) massaging the stomach, (6) clamping uring butta. The meaning of the symbols contained in the seven-monthly appassili procession lies in the procession of the tradition, namely: (1) passili leaves (lekok passili), (2) banana leaf shoots (bombong unti), (3) kakdok massingkuluk, (5) pots from the ground (uring butta), (6) lime (pakleok), (7) areca nut (pakrappo), (8) coins (doek rancing), (9) coconut (kaluku), (10) brown sugar ( golla eja), (11) water (jeknek), (12) candle (tai bani), (13) rice (berasak), (14) knife (lading), (15) wooden ladder (tukak pammakkang), (16) cake (kanrejawa picuru), (17) sweet banana (unti tekne), (18) fruits (rappo), (19) cooked eggs (bayao pallu), (20) grilled milkfish (jukuk bolu tunu), (21) pan (pammaja), (22) sarong (lipak ). In general, the meaning contained in the seven-monthly appassili procession of the Pasuleang II community of Takalar Regency is to obtain safety, sustenance, avoid danger / misfortune, a good life and prosperity in the family.Keywords: Symbolic meaning, Appassili seven-monthly, Semiotics of Charles Sanders Pierce